WANPRESTASI YANG MENGAKIBATKAN PERBUATAN MELAWAN HUKUM PADA PERJANJIAN PENGIKATAN AKTA JUAL BELI (PPAJB), (STUDI PUTUSAN NOMOR 44/PDT.G/2014/PN.JKT.SEL) - ERNI ARIYANTI (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Muhd. Yamin2. Tan Kamello3. Edy Ikhsan It is sometimes confusing to differentiate a default act from unlawful act. When a debtor does not return an object of rent, keeps taking the possession of and using it in spite of the expiry date, the creditor may file a lawsuit for default and unlawful act at the same time. How to differentiate an unlawful act from default according to the prevailing provisions and how the judge’s consideration in distinguishing these actions in the Ruling No. 44/Pdt.G/2014/PN.Jkt.Sel.An act of keeping a property which he has no right over it to the more rightful owner, and of not countering anything for using the property while the agreement term has been terminated is an unlawful act i.e. opposing against other person’s subjective rights and his own legal obligation; it is not regarded as violating the agreement because the agreement has been terminated. The consideration of the panel of judges who do not differentiate an unlawful act from a default in this case offends the defendant’s sense of justice. The consideration of the panel of judges who do not differentiate an unlawful act from a default in this case offends the defendant’s sense of justice.Keywords: Agreement, Sale and Purchase Deed Agreement, Default, Unlawful Act